2017
DOI: 10.5152/dir.2017.16499
|View full text |Cite
|
Sign up to set email alerts
|

Publication rates of abstracts presented at major interventional radiology conferences

Abstract: P resentation at research conferences serves as a valuable channel for individuals to share new knowledge and advances in a given clinical field. The ultimate goal of a conference presentation is usually subsequent manuscript publication. The process of submitting a manuscript for publication typically requires extensive peer review and revisions (1). Research quality plays a major role in whether a study is accepted by a journal. Therefore, assessing the rate at which presentations at major conferences are pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…29 However, this work was collated over 10 years. Given the reported mean time for radiology conference abstract to publication rates is 1.25 to 2 years, 15,19,[24][25][26][27]29,34 and the majority (>75%) of publications occur within 3 years, 16,[19][20]22,29,34 the findings of Adhikari et al may be an overestimation. Most conference abstracts resulting in a publication will occur within 5 years.…”
Section: Conference Abstract To Publication Ratesmentioning
confidence: 99%
See 3 more Smart Citations
“…29 However, this work was collated over 10 years. Given the reported mean time for radiology conference abstract to publication rates is 1.25 to 2 years, 15,19,[24][25][26][27]29,34 and the majority (>75%) of publications occur within 3 years, 16,[19][20]22,29,34 the findings of Adhikari et al may be an overestimation. Most conference abstracts resulting in a publication will occur within 5 years.…”
Section: Conference Abstract To Publication Ratesmentioning
confidence: 99%
“…Some studies were conducted in 5 years or less. 15,19,21,[26][27]30 One study reported an increased rate from 39% at 2 years post conference to 45% when extended to 3 years 3 months. 23 Similar findings were reported with an increase from 18.2% to 21.5% when data analysed only 2 months after the current year's 2019 ANZSNM conference was excluded.…”
Section: Conference Abstract To Publication Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…PubMed) on a regular basis to access original research articles [9] . Research quality is vital for manuscript publication acceptance and publication rate of conference presentations may be seen as a surrogate indicator of the quality of the scientific abstracts presented at a conference [10] . The publication rate of scientific abstracts presented at Emergency Medicine conferences outside Africa range between 15% and 35% [11] , [12] , [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%